The degree to which students and teachers are involved in second-level school processes and participation in decision-making: an Irish Case Study. Issue 2 (2nd April 2016) - Harrison, Kathy; Taysum, Alison; McNamara, Gerry; O'Hara, Joe
Abstract : The Education Act (1998 ) is a key policy document in Irish education, emphasising the rights, roles and responsibilities of key stakeholders, including parents, teachers and pupils in schools. Since 1998 the Department of Education and Skills (DES) has stressed the need to introduce an increased role for teachers and pupils in decision-making. It is therefore timely to explore the response of teachers and students to such a collaborative school environment in a rural second-level school of approximately 600 students. Transition year (TY) students (ages about 15–16) and their teachers were surveyed by questionnaire and interviewed. It finds that while the school is proactive in involving students and teachers in decision-making, a source of social, personal and professional empowerment, experienced teachers, and students in particular, want a more substantial voice. For example, most students want more say. They want class discussions or a vote, not just Student Council (SC) representation, on important and not just trivial issues. They want involvement before decisions are taken, with more feedback. Overall, participation is considered important by all stakeholders.